2023
DOI: 10.1021/acsami.3c03276
|View full text |Cite
|
Sign up to set email alerts
|

Engineering Active-Site-Induced Homogeneous Growth of Polydopamine Nanocontainers on Loading-Enhanced Ultrathin Graphene for Smart Self-Healing Anticorrosion Coatings

Abstract: Engineering nanocontainers with encapsulated inhibitors onto graphene has been an emerging technology for developing self-healing anticorrosion coatings. However, the loading contents of inhibitors are commonly limited by inhomogeneous nanostructures of graphene platforms. Here, we propose an activation-induced ultrathin graphene platform (UG-BP) with the homogeneous growth of polydopamine (PDA) nanocontainers encapsulated with benzotriazole (BTA). Ultrathin graphene prepared by catalytic exfoliation and etchi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 55 publications
(91 reference statements)
0
3
0
Order By: Relevance
“…The rapid rate of self-healing of BSL-80-70 is to blame for the aforementioned finding, further highlighting the critical function of self-healing double-layered design in preserving anticorrosion performance when physical damages occur. It can be shown from a comparison of the long-term | Z | f‑0.01 Hz in Figure b that, regardless of the state of modern self-healing coatings or traditional anticorrosion coatings, the | Z | f‑0.01 Hz typically decays at least two orders after 30 days at ambient temperature. The | Z | f‑0.01 Hz of EZ/BSL-80-70/PU is only less than an order of magnitude of attenuation decays after 200 days, thus exhibiting apparently increased durability.…”
Section: Resultsmentioning
confidence: 99%
“…The rapid rate of self-healing of BSL-80-70 is to blame for the aforementioned finding, further highlighting the critical function of self-healing double-layered design in preserving anticorrosion performance when physical damages occur. It can be shown from a comparison of the long-term | Z | f‑0.01 Hz in Figure b that, regardless of the state of modern self-healing coatings or traditional anticorrosion coatings, the | Z | f‑0.01 Hz typically decays at least two orders after 30 days at ambient temperature. The | Z | f‑0.01 Hz of EZ/BSL-80-70/PU is only less than an order of magnitude of attenuation decays after 200 days, thus exhibiting apparently increased durability.…”
Section: Resultsmentioning
confidence: 99%
“…However, when facing a complex service environment, the multi-functional anticorrosion coatings gradually attract more and more attention. These multi-functionalization anticorrosion coatings that are self-sensing, self-healing, wear-resisting, antibiosis and super-hydrophobic have intensively been developed to promote advanced applications [72]. To meet the demands of the multi-function in composite coatings, GO plays a significant role due to its excellent properties discussed above.…”
Section: Graphene Oxide-based Multi-functionalization Coatingsmentioning
confidence: 99%
“…1 μm, while the internal and external diameters are between 10–15 and 50–80 nm, respectively. ,, It is important to note that halloysite can be easily dispersed in water without the need for time-consuming exfoliation procedures required for other platy clays . Due to their attractive colloidal properties and versatile surface, , HNTs can be used in drug delivery, catalysis, remediation, nanocontainers for anticorrosive compounds, , and conservation of cultural heritage. , It is reported that halloysite modified by anionic surfactants produce inorganic micelles with solubilizing capacity toward hydrophobic molecules. , The filling of polymeric matrix with halloysite is proper to fabricate composite materials with excellent mechanical performances, vapor barrier properties, high thermal stability, and flame retardant characteristics. , Halloysite possesses peculiar interface properties since its outer and inner surfaces are oppositely charged within a large pH interval. Specifically, the surface cavity is positive, and the shell is negative for pH larger than ca.…”
Section: Introductionmentioning
confidence: 99%